The United Republic of Tanzania : Evaluation of the Poverty Reduction Strategy Paper Process and Arrangements under the Poverty Reduction and Growth Facility - IMF Independent Evaluation Office; Operations Evaluation Department (World Bank, Washington, DC, 2014)
This evaluation of the Poverty Reduction Strategy Paper (PRSP) and Poverty Reduction Growth Facility (PRGF) processes in Tanzania was jointly undertaken by the Operations Evaluation Department (OED) of the World Bank and the Independent Evaluation Office (IEO) of the IMF. The goal of the evaluation, as emphasized in the joint terms of reference, is to inform the policies and internal processes of the World Bank and the IMF, but not to evaluate the performance of the government. The report is laid out as follows: section two provides a background to the poverty situation in Tanzania as well as the economic and political context. The section also looks at the national strategies and processes for policy formulation that preceded the introduction of the PRSP and the PRGF. Section three discusses the Poverty Reduction Strategy Paper process in Tanzania, starting with a look at the relevance of the process to the key development challenges facing the country and then turns to the issue of how the underlying principles of the PRSP have been applied. It concludes with an analysis of the preliminary results.